Early Childhood Educators' Constructions of Play Beliefs and Practice - Parsons, Amy L. (Université d'Ottawa / University of Ottawa, 2013)
This qualitative study was designed to explore the constructions of Early Childhood Educators’ (ECE) beliefs about play and how they translate these beliefs into practice. Guided by a teachers’ beliefs framework (Sanger & Osguthorpe, 2011; Haney & McArthur, 2001; Richards & Lockheart, 1994; Pajares, 1992) and a constructivist philosophical lens, the study sought to identify (a) ECE educators’ beliefs about play, (b) how the educators practice play, and (c) how they incorporate both theoretical and practical components of play beliefs into the early childhood education classroom. A postmodern orientation and rigorous qualitative research methods were employed. Data were collected in three phases: an in-depth open-ended interview was conducted, followed by classroom observation over the course of 6 weeks, and finally a second interview was conducted using the process of Interpersonal Process Recall (IPR) with four purposefully selected participants. The interview data were transcribed and categories were co-constructed with the participants. Findings revealed that the educators came into their training programs with certain core beliefs about play that were developed in pre-service experience (upbringing, culture, childhood memories). These core beliefs played an important role in the information that these educators were able to filter into their previous beliefs about play. Further, the educators’ beliefs about play appeared to be reinforced and even magnified through their training programs, as they were able to take specific techniques and approaches and apply them in their practice. Two of the educators had previous experience working in daycare, hence facilitating the application of new knowledge to their pre-existing beliefs. The study findings add to a small growing body of research that furthers our understanding of the construction of early childhood educator beliefs. This research also helps us understand how educators’ pre-service and in-service experience contributes to the development of play beliefs and helps in the transfer of beliefs into practice. In addition, the findings give a voice to the early childhood educators, making a valuable contribution to the literature.